2016
DOI: 10.3389/fmars.2016.00084
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Binding Dissolved Organic Ligands in the Oxic and Suboxic Waters of the Black Sea

Abstract: In the oxygen-rich layer of the Black Sea, above the permanent halocline, the Fe and nitrate concentrations are low where fluorescence is relatively high, indicating uptake by phytoplankton. In this study we used ligand exchange adsorptive cathodic stripping voltammetry (CLE-aCSV), using 2-(2-Thiazolylazo)-p-cresol (TAC) as measuring ligand, to investigate the role of Fe-binding dissolved organic ligands in keeping Fe in the dissolved phase and potentially biologically available. The conditional stability cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 93 publications
(176 reference statements)
1
9
0
Order By: Relevance
“…Due to the high heterogeneity of E. huxleyi exudates, the oxidation rate, as well as the equilibrium and acidity constants, might represent an average value of the sum of the individual rates/constants weighted by the fraction of each species in solution (Rose and Waite, 2003). The theoretical range (10 17 -10 21 M −1 ) of the stability constant for the Fe(III)-L complex is in reasonable agreement with those found in the literature for ligands with bindings capacities lower than L 1 (Gledhill and Buck, 2012;Bundy et al, 2014;Gerringa et al, 2016), including those estimated by Boye and van den Berg (2000) in E. huxleyi cultures.…”
Section: The Kinetic Modeling Approachessupporting
confidence: 85%
“…Due to the high heterogeneity of E. huxleyi exudates, the oxidation rate, as well as the equilibrium and acidity constants, might represent an average value of the sum of the individual rates/constants weighted by the fraction of each species in solution (Rose and Waite, 2003). The theoretical range (10 17 -10 21 M −1 ) of the stability constant for the Fe(III)-L complex is in reasonable agreement with those found in the literature for ligands with bindings capacities lower than L 1 (Gledhill and Buck, 2012;Bundy et al, 2014;Gerringa et al, 2016), including those estimated by Boye and van den Berg (2000) in E. huxleyi cultures.…”
Section: The Kinetic Modeling Approachessupporting
confidence: 85%
“…There were concerns about the basin's large pH and Fe gradients, which are known to influence the optical properties of DOM. However, since the Black Sea's pH range of 7.3–8.2 is similar to the that found in the open ocean (Key et al ; Hiscock and Millero ), and dissolved Fe concentrations are no greater than ∼ 382 nM (Gerringa et al ; Rolison ), both pH and Fe concentrations should have negligible effects on the optical properties of DOM (Poulin et al ).…”
Section: Methodsmentioning
confidence: 58%
“…Anomalous DOC profile is at Sta. 6 in the Batumi Eddy, whichGerringa et al (2016) suggested to result from DOC removal being controlled by depth rather than r h , or perhaps resulting from the circulation within the Batumi Eddy. Note that three inflowing Sea of Marmara seawater samples from the Bosporus Strait station are excluded from (a) and (b).…”
mentioning
confidence: 98%
“…The valence, speciation, solubility, adsorption, organic complexation and rates of redox processes of transition metals are subject to influences by physicochemical conditions such as environmental pH, O 2 content and redox potentials ( Byrne et al, 1988 ; Banks et al, 2012 ; Sunda, 2012 ; Scholz et al, 2014 ). The properties of transition metals in marine environments are influenced by diverse biological factors as well ( Morel and Price, 2003 ; Gerringa et al, 2016 ). The recently proposed “Ferrojan Horse Hypothesis” highlights a newly discovered viral mechanism for the behaviors of Fe in marine environments ( Bonnain et al, 2016 ).…”
Section: Eco-energetic Responses Of Nitrogen-cycling Chemolithoautotrmentioning
confidence: 99%